A dislocation-driven laminated relaxation process in Si1−xGex grown on Si (001) by molecular beam epitaxy. (December 2021) - Xia, S.; Zhang, W.; Yuan, Z.; Li, J.; Ye, J.; Gu, Y.; Miao, Y.; Li, C.; Deng, Y.; Shen, A.; Lu, H.; Chen, Y.-F.
Abstract: Based on the successful epitaxial growth of Si1 − x Gex with a full spectrum of Ge content, we have grown a series of high-quality Si0.4 Ge0.6 films with different thicknesses on Si (001) substrates using molecular beam epitaxy. A laminated relaxation process is observed in the Si1 − x Gex samples above a certain thickness. Strain analyses by X-ray diffraction and high-resolution transmission electron microscopy have shown that the highly strained pseudomorphic layer can be preserved even after the relaxation has occurred. We propose a dislocation-driven relaxation mechanism and attribute this anomalous relaxation phenomenon to the low growth temperature used. This study shows that the manipulation of dislocation can be an effective way to enhance the growth of a highly mismatched heterostructure system.